CREATIVE AND INNOVATIVE COMMUNITY-BASED TOURISM MANAGEMENT IN TEGAL WARU, BOGOR - Nining Latianingsih; Iis Mariam; Dewi Winarni Susyanti (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2020)
Tourism provides a significant contribution to development, conventional tourism products are becoming increasingly abandoned and tourists are turning to tourism products that value the environment, nature, culture and special attractions more. How to manage tourist villages in the village of Tegal Waru Ciampea Bogor, in the flexibility and intensity of interaction with the environment and local communities. The purpose of this research is to see how the management of creative and innovative community-based tourism villages (CREANOVA) The approach method used is an empirical normative approach and uses qualitative methods and direct field research on research objects that are related to the problem under study. the results of the study are. Tegal Waru tourism village is a pedesan tourist area that is no less interesting and offers cultural potential. Has a variety of agricultural production businesses and entrepreneurs. Community participation in the development of tourist villages is very high. There are tour packages offered including entrepreneur training, charity creativity, outbound on the road, consumption packages, souvenir packages, shopping centers, tourism attractions, business tourist village locations, while visitors from home and abroad. Community participation is very high in implementing this village tourism program, because they feel an increase in income and economic life Keywords: Tourism Village Management Model, business, community participation, tegal waru, cultural potential